HABIB AND YOUTH RELATIONS IN BANYUWANGI - Atho’ilah Aly Najamudin; Mohamad Sahlan (International Conference on Humanity Education and Society (ICHES), 2023)
Lately Habib in Indonesia is still being discussed. This phenomenon becomes a serious problem in religious life. Social status as a descendant of the Prophet Muhammad Shallu alaihi wasalam provides social capital in the socio-religious structure. The Taklim Assembly is an arena in the formation of religious discourse. Habib formed a patron-client for the congregation. the majority of them, are young people. The character of young people has a great tendency to be curious, likes the challenge of forming a relationship between Habib as a religious leader and young people in forming religious relations. This paper will describe Habib and Young People in Banyuwangi, This is an effort to understand that the participation of young people in forming the Taklim Assembly as a social community, which is in a collection of associations consisting of several members with bonds of interdependence consciously and please help, in the context of youth activities is evidenced by the scheduled program which is a routine agenda every week. From the religious activities of Habib's children's lovers to form a religious community, then the activism of young Habib's lovers creates a social-religious movement, with three variables, first, the political process, where Habib has power in exercising religious authority. Second, the mobilization structure, namely Habib's ability to gather young people in religious activities. Third, in the framing process differentiation occurs in young people such as pious children, hijrah, and so on.